Strategi Sosialisasi Pendidikan Anti Narkoba, Psikotropika dan Zat Adiktif (NAPZA) di Era Modern : Studi Kasus Pada SMPN 1 Tebing Syahbandar - Sri Wahyuni; Kiki Rawitri; Bella Novia Sumantri; Devi Lola Viana; Karmida, Karmida; Khairil Azhari Nasution; Sofi Ayu (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research aims to evaluate the impact of anti-drug socialization activities held by Tebing Syahbandar District Community Service (KKN) students at SMPN 1 Tebing Syahbandar. A qualitative approach was used to gain an in-depth understanding of student and teaching staff participation, responses to various outreach activities, and the impact felt after implementing the activities. A preliminary study was conducted to collect information about school policies regarding drug abuse and understand the context of student life at SMPN 1 Tebing Syahbandar. The design of socialization activities involves identifying workshops, seminars and anti-drug campaigns, with adjustments to the activity design according to the needs and characteristics of students and teaching staff. The research results showed a high level of participation from students and teaching staff, with a positive response to the outreach activities. Interactive workshops, seminars with expert speakers, and creative campaigns have succeeded in providing relevant information, changing attitudes, and creating an environment of open dialogue in schools. Interviews with students and teachers revealed positive changes in knowledge, attitudes, and motivation to be actively involved in drug abuse prevention. Data analysis highlights the success of outreach activities in creating positive impacts, including increasing understanding and changing attitudes towards drugs. This research contributes to further understanding of the effectiveness of socialization strategies in the school environment and provides a basis for the development of similar activities in other educational institutions. The implication is that this approach can be adopted to increase awareness and prevent drug abuse among teenagers.